The Effective Development Techniques in Teacher Working Group Meeting to Improve Teacher Professionalism - Budi Wiyono, Bambang; Triwiyanto, Teguh (International Journal of Engineering and Technology, 2018)
The main objective of education is to develop human capabilities and personality. Moreover, the teacher is the major point in the implementation of education. To improve the quality of education, the professionalism of teachers should always be improved. One of the development techniques applied in Indonesia is teachers working group meetings. The purpose of this study is to find out the effective development techniques to improve professionalism in the teachers working group meetings. This research was conducted in Malang by using descriptive correlational research design. There were 110 teachers of elementary schools and junior high schools taken as samples using cluster proportional random sampling. Data collection techniques used questionnaires and documentation and analyzed by descriptive statistics and Pearson correlation. Based on the analysis results, it was concluded that the development techniques used in the Teacher Working Group meetings can be classified into five, namely lesson planning, doing workshops, teaching demonstration, lecturing, and having discussions. There is a significant positive correlation between teachersâ€™ participation in the Teacher Working Group meetings and their professionalism. The most effective development technique is teaching demonstration.Â Â